2011
DOI: 10.1172/jci58509
|View full text |Cite
|
Sign up to set email alerts
|

SCRIB expression is deregulated in human prostate cancer, and its deficiency in mice promotes prostate neoplasia

Abstract: Loss of cellular polarity is a hallmark of epithelial cancers, raising the possibility that regulators of polarity have a role in suppressing tumorigenesis. The Scribble complex is one of at least three interacting protein complexes that have a critical role in establishing and maintaining epithelial polarity. In human colorectal, breast, and endometrial cancers, expression of the Scribble complex member SCRIB is often mislocalized and deregulated. Here, we report that Scrib is indispensable for prostate homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
201
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(206 citation statements)
references
References 55 publications
5
201
0
Order By: Relevance
“…(17,48) HTLV-2 Tax2 protein has also been shown to play a crucial role in the immortalization ability of the virus. (17,18,43,49) We established peripheral T-cells immortalized by either Tax1 or Tax2, and the expression of MAGI-1 in these cells was determined. Our data indicated that while (15) were used as IL-2-dependent cells (lane 2-9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(17,48) HTLV-2 Tax2 protein has also been shown to play a crucial role in the immortalization ability of the virus. (17,18,43,49) We established peripheral T-cells immortalized by either Tax1 or Tax2, and the expression of MAGI-1 in these cells was determined. Our data indicated that while (15) were used as IL-2-dependent cells (lane 2-9).…”
Section: Resultsmentioning
confidence: 99%
“…Tax1 through the PBM has been shown to interact with cellular PDZ domain containing proteins, some of which are implicated in tumor suppression, (31)(32)(33) for instance deficiency of Scribble in mice induced prostate cancer through activating MAP kinase pathway. (49) Nevertheless, it remains unclear whether these PDZ proteins explain any of the Tax1 PBM functions or other cellular PDZ protein(s) play(s) a major role in Tax1 functions. The present study identifies MAGI-1 as a novel Tax1 interacting partner and found that Tax1 aberrantly sequesters MAGI-1 into Tax1 containing complexes and translocates it from the detergent-soluble to the detergent-insoluble cellular fraction (Figs 2,3).…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, SCRIB regulates apical-basal polarity and morphogenesis in epithelial cells (Bilder and Perrimon, 2000;Legouis et al, 2003), and spindle polarity in dividing neuroblasts (Albertson and Doe, 2003). In mammals, SCRIB regulates apical-basal polarity in epithelial cells (Qin et al, 2005;Godde et al, 2014;Pearson et al, 2011), front-back polarity in migrating astrocytes, T cells, fibroblasts and epithelial cells (Dow et al, 2007;Ludford-Menting et al, 2005;Nola et al, 2008;Osmani et al, 2006) and planar cell polarity of the stereociliary bundle in the inner ear cochlea (Montcouquiol et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests the conservation of a tumor suppressive role in mammals (Martin-Belmonte and Perez-Moreno, 2011;Pearson et al, 2011) as well as an important role in influencing the Hippo pathway (Cordenonsi et al, 2011). Currently there is thus much interest in understanding the fundamental activity of the Scrib module.…”
Section: Introductionmentioning
confidence: 99%